ANALISIS SPASIAL PERSALINAN DENGAN SEKSIO SESAREA DI INDONESIA SEBAGAI UPAYA MENURUNKAN KEMATIAN MATERNAL - Alfiyana Yuliasari; M. Sapoan Hadi; Tries Yuliastuti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2022)
Caesarean section is one of medical intervention in reducing maternal mortality rate (MMR) and infant mortality rate (IMR). However, the increasing number of caesarean sections did not affect the decrease in MMR and IMR. Some of the complications associated with caesarean section include endometriosis, postpartum haemorrhage, cystitis, and asphyxia. This study aims to describes the incident of caesarean section in Indonesia. The research method of this study is descriptive quantitative and ecological research design (place) with spatial data analysis from the 2017 IDHS data using Quantum GIS 3.4 software application. Population and sample of this study is all the pregnant women who gave birth in the cesarean section in 2012-2016 from all provinces in Indonesia are 2.648 people. Of all provinces in Indonesia, DKI Jakarta and Bali are the provinces with the highest incidence of caesarean section with of the proportion more than 30%. The majority of caesarean section incident increased in the two big cities due to several factors such as age and education. Overall, caesarean section is influenced by many factors. To decrease the high intervention of caesarean section, intervention efforts are needed on risk factors that can influence decision making for caesarean section.